Current update on herbal sources of antithrombotic activity-a comprehensive review - Bhavani Subramani; P. Sathiyarajeswaran (SpringerOpen, 2022)
Abstract Background Herbs are commonly used to treat cardiovascular diseases in various traditional medicine. On the other hand, herb-drug interactions are most commonly encountered with conventional antiplatelet and anticoagulant drug prescriptions. This review presents a compilation of plants investigated for antiplatelet and anticoagulation recently and enumerates their possible lead compounds responsible for its action for paving further drug discovery and knowledge update. Main body of the abstract Information about the herbs was withdrawn from the PubMed database of the previous 5 years. We also hand-searched the bibliography of relevant articles for the acquisition of additional information. About 72 herbal sources were identified with the effect of antiplatelet activity, antithrombotic activity, and anticoagulant activity. Bioactive compounds and various secondary metabolites responsible for it, such as alkaloids, saponins, flavonoids, coumarins, polyphenols, furan derivatives, iridoid glycosides, sesquiterpenes, aporphine compounds, were reported. Conclusion Newer pharmacological moieties are needed to prevent or reduce the adverse effects of current anti-thrombotic agents and to improve the safety of patients and cost-effectiveness.